Non-invasive transcranial alternating current stimulation of spatially resolved phosphenes - Sadrzadeh-Afsharazar, Faraz; Douplik, Alexandre (Frontiers in Neuroscience, 2023)
This study focused on the use of Non-Invasive Transcranial Alternating Current Stimulation (NITACS) to induce and map phosphenes (spark-like percepts in the visual field) in healthy individuals. The study found optimal stimulation parameters to induce reliable phosphenes without skin irritation or pain. The results suggest NITACS can be used as a tool to investigate the relationship between facial stimulation location and phosphene localization within the field of vision (FOV) and raise questions about the origin of phosphenes generated through NITACS. The outcomes of this study could serve as a source of inspiration for creating non-invasive visual aids in the future.